Methodological Proposal to Evaluate the Alternative of Outsourcing the Transportation Fleet of a Company - Quezada-Llanca, L (Elsevier B.V., 2019)
The companies have different solutions to transport their merchandise to the customer: have their own fleet, outsource the excess when the transport capacity is exceeded by the demand (mixed system) and the complete subcontracting of all the transport operations. Outsourcing is one of the solutions, in different areas of administration and especially in transportation. Then, being a strategic decision, it is pertinent to ask the questions: should it be externalized? and when?. The answer depends on factors that must be evaluated in each case. To make the decision, it is necessary first to evaluate if transport is a "key success factor" and it is a "basic competence" for the company. It is essential before defining what type of solution to give to the transport and depending on it, when it should be taken to make the business gain a competitive advantage. The proposed methodology distinguishes the relevant factors that allow a successful outsourcing, which are: people, infrastructure, ICTs, logistics management and business strategy, which will allow the development and growth of the business. Likewise, tools for business analysis, management, project evaluation and decision making, play a fundamental role in the qualitative and quantitative study of the proposed methodology, a decision model that allows the evaluation of the fleet s externalization, through the possible transport management solutions. Finally, a map of the evaluation process is proposed, integrating the tools defined for the diagnosis, evaluation and definition of the decision. © 2019 The Authors. Published by Elsevier Ltd.